2020
DOI: 10.1097/md.0000000000021373
|View full text |Cite
|
Sign up to set email alerts
|

The safety and effectiveness of rehabilitation exercises on COVID-19 patients

Abstract: Background: Corona Virus Disease 2019 (COVID-19) is spreading fast starting late 2019. It mainly affects the human respiratory system. Many reports revealed that rehabilitation exercise can improve respiratory function and relieve the pressure from diseases, but there is no evidence to prove its effects on COVID-19. This protocol of systematic review and meta-analysis will clarify the safety and effectiveness of rehabilitation exercises on different COVID-19 patients. Methods and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
0
14
0
5
Order By: Relevance
“…Altogether, currently, specific rehabilitation guidelines for long-COVID-19 patients are not available. Studies are needed to assess the effectiveness of programs and their safety [ 43 , 44 ]. The expertise of cardiopulmonary-rehabilitation services should also be considered [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, currently, specific rehabilitation guidelines for long-COVID-19 patients are not available. Studies are needed to assess the effectiveness of programs and their safety [ 43 , 44 ]. The expertise of cardiopulmonary-rehabilitation services should also be considered [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the “cardiorespiratory-exercise” profiles seem quite varied and also include patients who do not report a reduction in their performance (in comparison with the theoretical values according to age) [ 37 ]. On the other hand, the effect of cardiopulmonary-rehabilitation programs on long-COVID-19 patients is under investigation, but data are not yet available [ 43 ]. In total, the calculation of the required number of subjects is intricate.…”
Section: Discussionmentioning
confidence: 99%
“…Se o exercício de reabilitação puder ajudar no tratamento com COVID-19 ou melhorar a função respiratória e prevenir seus danos, beneficiará os pacientes e aliviando muito a pressão médica. Existem algumas complicações cardíacas tardias potenciais de COVID-19 que devem ser consideradas no retorno ao exercício após COVID-19, incluindo miocardite, devido ao risco de arritmias malignas e morte súbita (Gu et al, 2020).…”
Section: Importância Dos Exercícios De Reabilitação Para a Covid-19unclassified
“… 37 , 38 , 39 , 40 The reports demonstrated the safety and effectiveness of rehabilitation exercise for different COVID-19 patients. 41 Filgueira et al 42 discussed the effect of physical activity on the immune defense mechanism and its contribution to alleviating severe inflammatory response mediated by SARS-CoV-2. Tang et al found the dyspnea was alleviated of COVID-19 patients after 4 weeks of Liuzijue exercise.…”
Section: Exercise Intervention Helpful To Improve the Quality Of Life Of Covid-19 Patientsmentioning
confidence: 99%